Growth, secondary metabolites production, antioxidative and antimicrobial activity of mint under the influence of plant growth regulators - Parić, Adisa; Karalija, Erna; Čakar, Jasmina (Acta Biologica Szegediensis, 2017)
The effects of plant growth regulators on Mentha piperita explants cultured in vitro were studied for the purpose of analyse growth, secondary metabolite production, antioxidant and antimicrobial activities in micropropagated plants. The basal medium was experimentally supplemented with the auxin, indole-3-butyric acid (IBA) and the cytokinin, N6- benzyladenine (BAP) individually and in combination. Treatment with BAP and IBA resulted in an increased shoot and root number. The production of phenolic compounds was affected by the addition of the highest concentration of BAP, while antioxidant and antimicrobial activities were affected by several BAP and IBA treatments. Our results demonstrate that the application of growth regulators increases growth and secondary metabolite productions in the medicinal herb M. piperita.